KEDUDUKAN DAN STATUS HUKUM TERDAKWA PASCA PUTUSAN MAJELIS HAKIM YANG MENYATAKAN DAKWAAN JAKSA PENUNTUT UMUM KABUR (Study Putusan Pengadilan Negeri Rantauprapat No. 763/Pid.B/2020/PN-RAP ) - Muhammad Yusuf Siregar; Tintin Priatni Siregar (Universitas Labuhanbatu, 2021)
This study aims to analyze the legal aspects of the Position and Legal Status of the Defendant After the Decision of the Panel of Judges Declaring the Indictment of the Public Prosecutor Fleeing (Study of Decision of the Rantauprapat District Court No. 763/Pid.B/2020/PN-RAP). This research is Normative Empirical, namely research by looking at the conditions in the field by linking the legal sources of the regulations in force in the Republic of Indonesia. The benefits that will be received from the results of this study are to find out and analyze the position of the indictment which was declared vague and null and void as well as to find out and analyze the status and legal position of the defendant after the decision of the panel of judges which stated that the indictment of the public prosecutor was blurred in the Rantauprapat District Court Decision No. 763/Pid.B/2020/PN-RAP. The results of the study show that first, the position of the indictment which was declared vague and null and void in the Rantauprapat District Court Decision No. 763/Pid.B/2020/PN-RAP. 763/Pid.B/2020/PN-RAP is that based on the description of the first indictment, the Public Prosecutor mentions Iwan (not yet caught) but in the case file there is no letter or letter attachment from the Police in the form of Iwan being included in the People's Wanted List (DPO) because Therefore, the description of the Second Indictment of the Public Prosecutor is blurred so that based on the considerations above, the alternative indictment of the First Public Prosecutor is inaccurate and vague because it does not meet the requirements as referred to in Article 143 paragraph (2) letter b of the Criminal Procedure Code whose legal consequences are the alternative indictment of the First Public Prosecutor. null and void. Second, that from the series of legal processes mentioned above, it can be seen that even though at the district court level it was stated that the First and Second Indictments of the Public Prosecutor were null and void, but because the public prosecutor had filed an appeal with the decision ordered the Rantau Prapat District Court to continue the examination of this case until the final decision, the position of the defendant is still on trial and based on the final decision has sentenced the defendant to a sentence of 8 (eight) months imprisonment.Â Keywords: Legal Status, Indictment, Public Prosecutor.